2016
DOI: 10.1364/optica.3.000763
|View full text |Cite
|
Sign up to set email alerts
|

High-density hyperuniform materials can be transparent

Abstract: We show that materials made of scatterers distributed on a stealth hyperuniform point pattern can be transparent at densities for which an uncorrelated disordered material would be opaque due to multiple scattering. The conditions for transparency are analyzed using numerical simulations, and an explicit criterion is found based on a perturbative theory. The broad applicability of the concept offers perspectives for various applications in photonics, and more generally in wave physics.PACS numbers: 42.25.Dd, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
196
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(202 citation statements)
references
References 43 publications
(69 reference statements)
4
196
0
2
Order By: Relevance
“…To this purpose, we adopt a numerical approach allowing us to define, quantify, and independently vary all physical parameters of the scattering medium one at a time, encompassing for the first time, to the best of our knowledge, the whole parameter space in terms of both volume concentrations and spatial correlations. Here, we focus on the specific type of correlations induced by the packing of hard spheres, but our approach can be applied to any kind of spatial correlation in discrete systems, including deterministic aperiodic [41], potentialbased [42], hyperuniform [8], or random fractal [43] structures. Owing to this richer characterization, novel insight is gained by analyzing the interplay between particle density and spatial correlations in terms of two key functionals of the 3D point statistics, namely the first moments of the nearest-neighbor distance and pore-size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…To this purpose, we adopt a numerical approach allowing us to define, quantify, and independently vary all physical parameters of the scattering medium one at a time, encompassing for the first time, to the best of our knowledge, the whole parameter space in terms of both volume concentrations and spatial correlations. Here, we focus on the specific type of correlations induced by the packing of hard spheres, but our approach can be applied to any kind of spatial correlation in discrete systems, including deterministic aperiodic [41], potentialbased [42], hyperuniform [8], or random fractal [43] structures. Owing to this richer characterization, novel insight is gained by analyzing the interplay between particle density and spatial correlations in terms of two key functionals of the 3D point statistics, namely the first moments of the nearest-neighbor distance and pore-size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 A major focus of this paper is the study of a particular property of the void space between point particles in disordered "stealthy" systems, [15][16][17][18][19] which are disordered many-particle configurations that anomalously suppress large-scale density fluctuations, endowing them with unique physical properties. [20][21][22][23][24][25] The specific question that we investigate is whether disordered stealthy systems can contain arbitrarily large holes. Here we define a "hole" as a spherical region of a certain radius that is empty of particle centers.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems have received considerable attention because they anomalously suppress density fluctuations. [20][21][22][23][24][25] Specifically, if one places a spherical window of radius R into a d-dimensional many-particle system and counts the number of particles in the window, then the number variance, σ 2 (R), scales as R d for large R in typical disordered systems. Any system in which σ 2 (R) grows slower than R d is said to be hyperuniform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It has also been shown that dielectric networks derived from stealthy disordered hyperuniform point configurations possess complete photonic band gaps comparable in size to those of a photonic crystal, while at the same time maintain statistical isotropy, enabling waveguide geometries not possible with photonic crystals as well as high-density disordered transparent materials. 17,[27][28][29] However, the determination of physical/chemical properties of stealthy disordered hyperuniform materials is generally an unexplored area of research.…”
mentioning
confidence: 99%